Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/03014460.2014.934920
|View full text |Cite
|
Sign up to set email alerts
|

Age as a moderator of the secular trend for grip strength in Canada and the United States

Abstract: The results are contrary to what might be expected given that body weight has increased in both countries in recent decades and given that grip strength has been found to be positively correlated with body weight. It is suggested that there was a concurrent change in a factor that operated to counteract the effect of increased body weight on grip strength, a prime candidate being a decrease in levels of serum vitamin D. It is also suggested that the secular decline in adult grip strength can be explained by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
2
10
0
Order By: Relevance
“…This may be due to lower fat-free mass in underweight children and higher fat-free mass in obese children. These results are in accordance with a previous study by Silverman et al [20] who were researched the trend of handgrip strength of children in the United States and Canada. It was found that there is a positive correlation between body mass and handgrip strength.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to lower fat-free mass in underweight children and higher fat-free mass in obese children. These results are in accordance with a previous study by Silverman et al [20] who were researched the trend of handgrip strength of children in the United States and Canada. It was found that there is a positive correlation between body mass and handgrip strength.…”
Section: Discussionsupporting
confidence: 93%
“…The relative grip strength in the operated and un-operated (dominant) hand has remained similar over time, 95% (95/100 kg) in the 41-months follow-up and 84% in the 40-year follow-up (53/63 kg). The reduction in strength is similar to the decline in strength that occurs with age in the general population [32]. The ROM at various early follow-up times in seven of the cases are displayed in Table 1.…”
Section: Discussionsupporting
confidence: 58%
“…We might, therefore, have expected to see greater strength in the more recent waves as opposed to a slight decline. A potential explanation for this discrepancy is the hypothesis that cumulative exposure to raised BMI earlier in the life course might have deleterious effects on grip strength, perhaps due to persistent exposure to a pro-inflammatory state [19]. This idea is supported by the finding that raised BMI across adulthood is associated with reduced upper limb muscle quality in early old age [20].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%